AKINETES FORMATION AND GERMINATION IN CYLINDROSPERMUM MAJUS KUTZ. - JAWAD, ABDUL-LATEEF M. (Iraqi Journal of Aquaculture, 2022)
Were made from different water and soil samples. Akinetes formation was observed during the incubation of samples (cultures) at 4ºC for six months period. Germination of akinetes took place only after transferring the isolate to a new culture media at 26ºC. The gradual steps of akinetes germination were followed and illustrated for the first time in this species. The results showed that the outer most layer may expand to the available references do reffer to such calyptra formation and such growth and development.